The The Ideological Dialectic Between Islam and the State in the Formulation of Indonesia’s State Principles: From Constitutional Compromise to Public Ethics: From Constitutional Compromise to Public Ethics - Joni Harnedi; Danil Mahmud Chaniago; Rahmad Tri Hadi (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The linkage between Islam and the state in Indonesia has been analyzed in terms of history, constitution, and politics. Nonetheless, prior research has considered BPUPKI,  Piagam Jakarta (Jakarta Charter), and Constituent Assembly discussions as individual constitutional issues without understanding their interrelated ideologies. Therefore, this paper aims to explore the ideological negotiation between Islam and nationalism in the construction of Indonesia's state foundation through qualitative historical methodology of document analysis and political philosophy interpretation. Primary data includes BPUPKI and PPKI's discussion, Piagam Jakarta, and Constituent Assembly discussions with the help of secondary sources. The results demonstrate that the construction of the state foundation in Indonesia was an ideology-mediated process but not a constitutional one. Piagam Jakarta is the manifestation of constitutional compromise, whereas Constituent Assembly discussion represents the continuing reinterpretation of the relation between religion and the state in a pluralistic democracy. The author suggests the model of Indonesian Ideological Mediation that proves that the relationship between Islam and the state develops as a result of constitutional compromise, ideological mediation, and ethical transformation. Instead of instituting Islam as the basis of the state formally, the suggested model treats Islamic ideology as public ethics incorporated into Pancasila and constitutional democracy.